Academic Collaboration and Technological Innovation in Kenyan Public Universities: An Innovation Intermediary Perspective - Caroline Awuor Odhuno; Kenneth Lawrence Wanjau; Richard Kiai (Journal of Policy and Development Studies (JPDS), 2026)
Kenya’s public universities are central to the country’s innovation agenda, yet weak linkages with industry continue to constrain technology transfer. This study examines how academic collaboration influences technological innovation and evaluates the dual role of innovation intermediaries as mediators and moderators in this relationship. A cross‑sectional survey design was adopted, with a census of all 66 chartered universities and stratified random sampling of industry and intermediary respondents, yielding 212 participants. Data were analysed using covariance‑based structural equation modelling (CB‑SEM) in AMOS. Results indicate that academic collaboration exerts a significant positive effect on technological innovation. In contrast, innovation intermediaries both transmit collaborative inputs into outcomes (partial mediation) and strengthen the collaboration–innovation link (positive moderation). These findings highlight the need for universities to embed innovation more deliberately into collaborative structures by strengthening intermediary capacity. Policy implications include investment in incubation infrastructure, technology transfer mechanisms, and enabling frameworks that accelerate commercialisation and knowledge exchange. The study contributes to scholarship on university–industry collaboration by demonstrating that intermediaries serve a dual role in amplifying innovation outcomes in an emerging-economy context.